Overcoming incontinence a straightforward guide to your options - Dierich, Mary (John Wiley & Sons, 2000)
This text offers a step-by-step plan that starts with natural, conservative methods, and moves to the groundbreaking advances in care and treatment. It provides options for treating urinary incontinence - from simple lifestyle changes and exercises to devices, medications, and surgery.